Scaffolding interdisciplinary project-based learning: a case study. (3rd May 2020) - MacLeod, Miles; van der Veen, Jan T.
ABSTRACT: Can you ask students from three different bachelor programmes to help solve planning and routeing problems for hospitals? In the presented case an interdisciplinary approach was shown to be successful after some redesign. Students from Applied Mathematics, Civil Engineering and Industrial & Engineering Management jointly designed solutions for 'traffic' to and through the hospital using stochastic modelling. Importantly this project was scaffolded through coursework, supervision and problem-design. The particular scaffolding strategy employed by the teaching team offers other teacher teams ideas for making interdisciplinary project-based learning a more effective learning opportunity. At the same time we need to ensure that students feel at home in their own programme and will be empowered to work with other specialists.